Case Report: Endovascular embolization under DSA for multivessel supply mixed pulmonary sequestration in young patients - Li, Hong; Li, Qinhong; Zhang, Xing; Li, Feng; Su, Zhongjian; Deng, Lili; Gong, Chuxiong (Frontiers in Cardiovascular Medicine, 2025)
Pulmonary sequestration (PS) is a rare congenital lung developmental anomaly characterized by abnormal lung tissue that receives its blood supply from the aorta. Among the various types, mixed PSrepresents a distinct subtype. Currently, there is a lack of definitive reports regarding the specific management of this condition in infants and young children. We report a case of a 1-year-old patient with mixed PS treated with endovascular occlusion under digital subtraction angiography (DSA). Given the patient's young age and the complexity of the vascular malformation, we opted for endovascular intervention rather than surgery. Utilizing the Seldinger technique, we accessed the right femoral artery and vein for angiography, confirming the abnormal vessels supplying the pulmonary cyst. Subsequently, we placed vascular embolization devices to achieve closure. Postoperatively, the patient did not experience any significant complications. Follow-up revealed substantial absorption of the PS, disappearance of the abnormal vessels originating from the descending aorta, and no recurrence of respiratory infections. This case highlights the efficacy of endovascular intervention in young patients with complex vascular mixed PS.